2011
DOI: 10.1007/s13143-011-0008-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grid size on building wind according to a computation fluid dynamics simulation

Abstract: Skyscrapers negatively impact the environment by creating gusty winds, known as building winds, which are the result of descending turbulences caused by the blockage of upper air by tall buildings. Usually, a building wind impact assessment (BWIA) is carried out using a wind tunnel test or computation fluid dynamics (CFD) simulation methods. The application of wind tunnel test is limited by the high costs of the models. Thus, CFD simulations are now the preferred approach to save time and expense as a result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The resolution of the grid seriously affects the accuracy of the simulation results. Kim et al [40] used grids with a size of 2.5 m × 2.5 m and 8 m × 8 m respectively to simulate a building area consisting of 9 high-rise buildings, and found that the velocity results between these two grids differs up to 11 m/s under certain wind direction.…”
Section: Computational Grid Divisionmentioning
confidence: 99%
“…The resolution of the grid seriously affects the accuracy of the simulation results. Kim et al [40] used grids with a size of 2.5 m × 2.5 m and 8 m × 8 m respectively to simulate a building area consisting of 9 high-rise buildings, and found that the velocity results between these two grids differs up to 11 m/s under certain wind direction.…”
Section: Computational Grid Divisionmentioning
confidence: 99%
“…Many scholars have verified the calculation accuracy of different turbulence models based on tetrahedral and hexahedral meshes under different conditions for high-rise buildings [14][15][16][17][18]. For instance, Murakami and Mochida compared the CFD simulation results with wind tunnel experiment results and found that the k-ε model could predict velocity and pressure fields well under fine-mesh conditions [19].…”
Section: Introductionmentioning
confidence: 99%